Atlas of male genitourethral surgery : the illustrated guide - Muneer, Asif; Arya, M. (Manit); Jordan, Gerald H. (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
Male genitourethral abnormalities are a source of great concern and distress to those affected. Surgery, when required, is very specialized and often extremely complex requiring expert surgical skills in order to achieve the best outcomes. Atlas of Male Genitourethral Surgery: The Illustrated Guideprovides urological surgeons, at all levels of experience from trainees to established specialists, with a full colour, highly illustrated and step-by-step approach to male genitourethral surgery, enabling complete mastery of surgical techniques in this difficult and challenging.
Front matter -- Surgical anatomy of the male external genitalia / Vishy Mahadevan -- Basic perioperative considerations for genitourethral surgery / Rahul Mistry, Iqbal S Shergill, Manit Arya, Anthony R Mundy -- Basic surgical techniques / Afshin Mosahebi, Alex CS Woollard -- Congenital penile abnormalities / Nicol C Bush, Warren T Snodgrass -- Surgical management of cryptorchidism and testicular tumors / Manit Arya, Imran Mushtaq, Abraham Cherian -- Surgery for penile curvature / Laurence A Levine, Jonas S Benson, Asif Muneer -- Surgery for erectile dysfunction / Majid Shabbir, Asif Muneer, Suks Minhas -- Augmentation procedures for the penis / Giulio Garaffa, Salvatore Sansalone, David J Ralph -- Surgery for male infertility / Nim Christopher, Asif Muneer -- Urethral reconstruction and artificial urinary sphincters / Daniela E Andrich, Anthony R Mundy -- Surgical treatment of penile cancer / Simon Horenblas, Peter R Malone, Asif Muneer -- Penile and scrotal reconstruction / Giulio Garaffa, David J Ralph, Peter R Malone -- Surgery for benign scrotal and foreskin conditions / Laurence A Levine, Jonas S Benson, Rowland Rees -- Surgical management of genitourethral emergencies / Rowland Rees, Duncan Summerton, Nim Christopher, David J Ralph.
Edition statement from running title area.
Includes bibliographical references and index.
Online resource; title from resource home page (ebrary, viewed on January 20, 2015).
Keywords: Generative organs, Male -- Surgery; Penile Diseases; Penis; Urogenital Surgical Procedures; Medicine; Penile diseases -- Surgery -- Atlases; Penis -- Surgery -- Atlases; Urogenital surgical procedures -- Atlases; MEDICAL -- Surgery -- General; Generative organs, Male -- Surgery; Atlases; Electronic books